INDICES OF THE CELL CYCLE IN THE THYROID GLAND AFTER THERMAL BURNS OF THE SKIN WHEN USING SOLUTIONS OF LACTOPROTEIN WITH SORBITOL OR HAES-LX 5 % - Tiron, O.I.; Appelhans, O.L.; Gunas, V.I.; Chereshniuk, I.L.; Lysenko, D.A. (World of Medicine and Biology, 2020)
The DNA content in the nuclei of thyroid cells of 90 white male rats on the background of skin burns of 2-3 degrees (with a lesion area of 21-23 % of the body surface) and the introduction of solutions of lactoprotein with sorbitol or HAES-LX 5 % was determined by flow cytometry. At 1, 3, 7 and 14 days after thermal trauma to the skin and the use of lactoprotein with sorbitol or HAES-LX 5 %, only lower values of S-phase values were found compared to the groups without burns. 21 days after thermal damage to the skin in the group with infusion HAES-LX 5 %, the interval SUB-G0G1 is significantly higher than in the control group. After 30 days in the groups with prior administration of HAES-LX 5 % and lactoprotein with sorbitol solutions, the value of SUB-G0G1 is significantly higher than that in the groups without skin burns.